2019
DOI: 10.1111/cea.13443
|View full text |Cite
|
Sign up to set email alerts
|

Should testing be initiated prior to amoxicillin challenge in children?

Abstract: Amoxicillin is the most common antibiotic prescribed in children with increasing use over time. While up to 10% of children are labelled as amoxicillin allergic, most children can tolerate amoxicillin after allergy evaluation. It is well documented that the label of amoxicillin allergy in children is associated with adverse health outcomes such as antibiotic-resistant infections. However, it remains controversial how best to assess children for amoxicillin allergy. While in general it is recommended that skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…42 Although up to 10% of children are labeled as beta-lactam allergic, approximately 90% to 99% of them tolerate amoxicillin after allergy evaluation. 43,44 The label of beta-lactam allergy is associated with significant unintended consequences including higher health care costs. 45 A systematic review found that the label of beta-lactam allergy was associated with an average excess of $1145 to $4524 in patient costs per patient.…”
Section: Efficientmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Although up to 10% of children are labeled as beta-lactam allergic, approximately 90% to 99% of them tolerate amoxicillin after allergy evaluation. 43,44 The label of beta-lactam allergy is associated with significant unintended consequences including higher health care costs. 45 A systematic review found that the label of beta-lactam allergy was associated with an average excess of $1145 to $4524 in patient costs per patient.…”
Section: Efficientmentioning
confidence: 99%
“…49 However, skin testing has poor sensitivity (<20%) and poor positive predictive values (<10%), and skin test reagents are costly, can be difficult to obtain, and have short half-lives once diluted. 43 In addition, a drug provocation test without prior skin testing is safe and effective in diagnosing beta-lactam allergy without skin testing. 50 There is a push for direct provocation testing without prior skin testing, especially in lower risk patients in whom the mechanism of suspected reaction is unlikely to be IgE-mediated.…”
Section: Efficientmentioning
confidence: 99%
“…Several studies show a tendency of over-prescribing antibiotics without a clinical indication, in numerous dental pathologies such as irreversible pulpitis, dental abscess or even for pain management [1,11,24,28,29]. Goel et al emphasize the importance of four criteria in antibiotic prescription: choosing the appropriate antibiotic, the right dosage, the precise period of administration and choosing, as much as possible, the antimicrobial substance aimed to the pathogen [3].…”
Section: Inadequate Use Of Antibioticsmentioning
confidence: 99%
“…55 Considering NSAIDs, it has been reported that a dose of 500 mg of aspirin is sufficient to differentiate between cross-intolerance and selective responders. 56 Finally, controversies exist about the reported safety and cost-effectiveness of direct DPT without previous STs for penicillin allergy delabeling in low-risk patients, [57][58][59][60] while others recommend to perform it with the culprit in all children with suspected BL hypersensitivity. 61 Importantly, the last position paper from the EAACI, in patients with BL allergy, recommends this procedure in children with mild maculopapular exanthema, although it is not recommended in adults experiencing low-risk NI-DHRs other than palmar exfoliative exanthema.…”
Section: Drug Provocation Testmentioning
confidence: 99%